THE FIGHT AGAINST SMOKING IN THE COUNTRIES OF THE WORLD AND IN UZBEKISTAN - Alimova, Sabokhat Gazievna (Scholar Express Journals, 2024)
This article examines current issues of youth, such as smoking and spending money on tobacco products. Based on public data, a lot of young people believe that a pack of cigarettes smoked by them only affects their health, and we claim that it hits their wallet. There are countries where tobacco products cost pennies, and when buying this product, a person does not think about its cost. However, there are still people among the youth with common sense in life, and they are well-versed in the market economy and have a financially literate ideology.
Keywords: tobacco; financial literacy; products; healthy lifestyle